Direct effect of interactive mobile learning approach towards renewable energy on children in Malaysia - Siti Umaira Zakaria; Sahriah Basri; Mismisuraya Meor Ahmad; Siti Kartom Kamarudin (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
Renewable energy (RE) is getting more attention in solving the escalating global warming issue. However, the community has not been sufficiently educated about this fact. Exposure to renewable energy technology in Malaysia, especially for children, is still lacking, leading to a lack of awareness on the importance of renewable energy. Besides, children’s lack of knowledge about renewable energy and lack of interest in the field of science became problems in this study. Therefore, this study on effect of usefulness, user friendly, quality and user acceptance toward mobile application approach in introducing knowledge of renewable energy. The main software in developing the RE application consist of five components, i.e. introduction, video, game, quiz and news. Testing was carried out on selected children to evaluate children’s satisfaction in terms of using the application in learning RE. A pilot study was conducted on 30 children and the application model was validated by three experts and evaluated for its effectiveness through quantitative studies. Then, the mobile apps were tested on 77 9-year-old children with a quantitative research method to assess the level of knowledge acceptance and awareness of renewable energy. Results indicate that the children’s knowledge of RE increased with the use of this RE mobile application because RE information is delivered in the form of images, audios, and videos. More than 98% of the respondents agree that the application helps in understanding RE. The mobile application also successfully attracted the children’s interest in RE innovation and increased their awareness on the importance of RE.